The value of the composite function fog(1) is -1
Explanation:
Step 1 :
Given,
f(-2) = -1
g(1) = -2
We need to find (fog)(1)
Step 2 :
Function f(2) means the value of the function f when x = 2
fog refers to composite function f(g(x)), that is evaluate the function g for x and then evaluate the function f for the result
So to find the composite function (fog)(1) we need to find g(1) first and then apply the function f on the result.
so g(1) = -2
f(g(1))=f(-2) = -1
fog(1) = -1
Step 3 :
Answer :
The value of the composite function is -1